The story of intracerebral hemorrhage - Broderick, Joseph; Grotta, James C.; Naidech, Andrew M.; Steiner, Thorsten; Sprigg, Nikola; Toyoda, Kazunori; Dowlatshahi, Dar; Demchuk, Andrew M.; Selim, Magdy; Mocco, J; Mayer, Stephan (Stroke, 2021)
This invited special report is based on an award presentation at the World Stroke Organization/European Stroke Organization Conference in November of 2020 outlining progress in the acute management of intracerebral hemorrhage (ICH) over the past 35 years. ICH is the second most common and the deadliest type of stroke for which there is no scientifically proven medical or surgical treatment. Prospective studies from the 1990s onward have demonstrated that most growth of spontaneous ICH occurs within the first 2 to 3 hours and that growth of ICH and resulting volumes of ICH and intraventricular hemorrhage are modifiable factors that can improve outcome. Trials focusing on early treatment of elevated blood pressure have suggested a target systolic blood pressure of 140 mm Hg, but none of the trials were positive by their primary end point. Hemostatic agents to decrease bleeding in spontaneous ICH have included desmopressin, tranexamic acid, and rFVIIa (recombinant factor VIIa) without clear benefit, and platelet infusions which were associated with harm. Hemostatic agents delivered within the first several hours have the greatest impact on growth of ICH and potentially on outcome. No large Phase III surgical ICH trial has been positive by primary end point, but pooled analyses suggest that earlier ICH removal is more likely to be beneficial. Recent trials emphasize maximization of clot removal and minimizing brain injury from the surgical approach. The future of ICH therapy must focus on delivery of medical and surgical therapies as soon as possible if we are to improve outcomes.
Gesehen am 12.07.2021